Applying a unified process kinetic equation to advanced materials process analysis: Characterization of the kinetics of isothermal microwave‐assisted chemical syntheses - Boon Wong (Engineering Reports, 2023)
Abstract Rate‐enhancement of any isothermal, isobaric chemical synthesis conducted under resonant microwave (RM) irradiation versus the same process activated by conventional field‐free heating has been attributed to a reduction in activation enthalpy of the process. This report applies a unified process kinetic equation (UPKE) to demonstrate and characterize non‐thermal microwave effects (NTME) on kinetics‐enhancements observed in isothermal microwave‐assisted chemical syntheses (IMACS). The UPKE, derived from a mesoscopic irreversible thermodynamic model, pinpoints that the rate of any high‐affinity chemical reaction is effectively independent of the affinity of the process as described by the mass‐action rate law. Energetically, activation enthalpy reduction observed in IMACS is considered the major NTME, which causes dominant process‐rate enhancements. This NTME results from RM‐induced enthalpy variation during the reaction: RM energy‐input first promotes the molar enthalpy of the irradiated reactant(s) at temperature, which consequently motivates an activation enthalpy reduction for rate‐enhancement. Conversely, frequency coefficient lowering is another common NTME occurring in IMACS, causing an adverse yet compensable setback to process‐kinetics as predicted by the UPKE. Applicability of the UPKE‐proposed rationale and methodology for IMACS kinetic characterization is fully confirmed by relevant data in the literature.